"The whole process has passed with awareness": A field experience story of pre-service physical education teacher - Atakan Yahyaoglu; Ozlem Alagul (ümit doğan üstün, 2021)
One of the most important factor for students to have real learning experiences is the professional development of their teachers. In recent years, it is recommended to investigate the process of professional learning, especially in physical education teacher education (PETE) programs, by focusing on learning processes that include students, administrators, and the physical conditions of the teaching environment, as well as the individual characteristics of teachers in professional development approaches. The most important opportunity that brings together all stakeholders in PETE programs is field experiences. In this study, the awareness of teaching framework (Rodriguez and Fitzpatrick, 2014) was used to understand of professional learning through field experiences of a pre-service physical education teacher. The aim of this study, which was designed with action research, was to explore the awareness of a pre-service teacher in both the teaching practice course in a high school context, and the peer-mentoring in the courses in the PETE program. In the findings of the study, while mentoring the peers of the pre-service teacher at the same level; he realized that his knowledge was constantly questioned by his peers, so peer-mentoring increased his content knowledge. Another awareness is experienced; the pre-service teacher makes the course preparation in accordance with the curriculum and the readiness of the students, as well as taking into account the students' past experiences and current needs. Finally, when the pre-service teacher interacts with the students positively in a real environment and answers each question with giving importance, he realizes that they are teaming up with students. As a result, if pre-service teachers are enabled to experience environments that will realize their difficulties as self-sufficient individuals in PETE programs, it will be effective in ensuring that they adopt and develop their own professional learning as learners throughout their careers.